Pd ultra-small clusters as precursors for silica-encapsulated Pd nanoreactors: highly sinter-resistant catalysts - Samanta, Anupam; Devi, R. Nandini (Chemcatchem, 2013)
Sintering and consequent deactivation in supported metal catalysts is a severe problem encountered in heterogeneous catalysis. This problem can be addressed by encapsulating active metal nanoparticles within inert oxides such as silica, provided the oxide shell is porous to enable access of reactant molecules to the nanoparticle surface to facilitate catalysis. We report the synthesis of highly sinter-resistant silica-encapsulated Pd catalysts with nanoparticle sizes stabilized at (3.4 +/- 0.6)nm at high temperatures of approximately 750 degrees C. The synthesis was achieved by utilizing thiol-protected ultra-small clusters of Pd as precursors for silica encapsulation. The ultra-small clusters were synthesized by using propyl ammonium functionalised thiols making them water-dispersible and amenable for silica encapsulation. Abundance of organics also aided in creating porosity subsequent to calcination at high temperatures.
Keywords: cluster compounds; Encapsulation; nanoreactors; Palladium; silicates

Photocatalytic H-2 evolution from water-methanol system by anisotropic InFeO3(ZnO)(m) oxides without cocatalyst in visible light - Narendranath, Soumya B.; Yadav, Ashok Kumar; Bhattacharyya, Dibyendu; Jha, Shambhu Nath; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2014)
InFeO3(ZnO)(m), series of oxides are found to give unprecedented H-2 evolution from water-methanol mixtures without using any cocatalysts. This family of compounds has an anisotropically layered structure in which Zn/FeOn polyhedra are sandwiched between InO6 octahedral layers. Local structure characterization by X-ray absorption spectroscopy reveals that Zn coordination changes from pentacoordinated to tetrahedral geometry across the series, whereas Fe geometry remains trigonal bipyramidal in all the compounds. This peculiar structure is conducive for a spatial separation of photogenerated charges reducing recombination losses. Band gap energies calculated from absorption spectra indicate potential visible light activity, and this may be due to the orbital mixing of Fe 3d and O 2p as revealed by pre-edge features of X-ray absorption spectra. Band positions are also advantageously placed for a visible light H-2 generation and is indeed found to be the case in methanol-assisted water splitting with standardized hydrogen evolution of similar to 19.5 mmol g(-1) h(-1) for all the catalysts.
Keywords: anisotropic structure; H-2 evolution; InFeO3(ZnO)(m); layered oxide; photocatalytic water splitting

Pt States in BaCe0.98Pt0.02O3-delta during start up and shut down operations under different conditions: stability and activity of ionic Pt in water gas shift reaction - Rajesh, Thattarathody; Devi, R. Nandini (Catalysis Letters, 2014)
Stability of Pt species in doped BaCeO3 perovskites under Water gas shift reaction conditions is studied using X-ray absorption spectroscopy and in situ powder X-ray diffraction. The catalyst BaCe0.98Pt0.02O3-delta has Pt in +2 oxidation state and is found to be stable in the ionic form under reaction conditions as well as under various highly reducing shut down and start up conditions. In-situ XRD under Water Gas shift reaction conditions also reveals the Pt ions to be highly stabilized in lattice and no egress is observed.
Keywords: BaCeO3; Deactivation; platinum; WGS reaction; XPS

Photocatalytic H-2 evolution from water-methanol mixtures on InGaO3(ZnO)(m) with an anisotropic layered structure modified with CuO and NiO cocatalysts - Narendranath, Soumya B.; Thekkeparambil, Saranya V.; George, Leena; Thundiyil, Shibin; Devi, R. Nandini (Journal of Molecular Catalysis A-Chemical, 2016)
InGaO3(ZnO)(m) series of oxides is found to be active for photocatalytic H-2 evolution from water-methanol mixtures. The structure of this series is highly anisotropic with InO6 octahedral layers sandwiching Ga/ZnOn polyhedra. The structural anisotropy in which the conducting layer is spatially separated from the charge generation sites may help in suppressing charge recombination and consequently enhance catalytic activity. The band gaps of the series obtained from absorption spectra are above 3.6 eV and hence they are not active under visible light irradiation. H-2 evolution is considerably enhanced under UV light on employing NiO as cocatalyst due to facile electron transfer from InGaO3(ZnO)(m). to NiO. However, when CuO is used as cocatalyst, visible light activity could be brought out. Due to the very low band gap of CuO, it can act as a sensitizer absorbing in visible light. The band positions become conducive for H-2 evolution due to band alignments consequent to electron accumulation in CuO conduction band. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: InGaO3(ZnO)(m); photocatalytic water splitting; visible light; XPS; XRD